ROLE OF NON ENTREPRENEUR PARENTS AND ENTREPRENEURIAL EDUCATION IN IMPROVING INTEREST OF ENTREPRENEURSHIP IN HIGH SCHOOL XII STUDENTS - Aji, Imanuel Deny Krisna; Sigar, Natalia Vike Theresia (Jurnal Entrepreneur dan Entrepreneurship, 2018)
The high unemployment rate in Indonesia is due to a lack of entrepreneurship. This situation occurs because people prefer to work as employees in the company rather than to run their own business. If the entrepreneurship interest in the community is low, efforts need to be made to increase that interest, especially for the younger generation. This study aims to determine the effect of entrepreneurship education and the role of parents as independent variables on the interest in entrepreneurship (dependent variable) high school students of class XII CB. The subjects of this study were all students of class XII CB. The type of research used in this study is quantitative descriptive. The data were collected using a questionnaire (questionnaire) with a Likert scale. Validation using Pearson showed correlation with a significance rate of 0.05 (5%). The population of students of Class XII CB High School involved 28 students. This study found that entrepreneurship education and the role of parents had a linear relationship to the interest in entrepreneurship significantly. The correlation test showed a strong correlation (0.719) between entrepreneurship education and the role of parents with an interest in entrepreneurship. The coefficient of determination Adjusted R square was 0.479 (47.9%), meaning that the independent variable has a strong percentage in explaining the dependent variable. The results of the t test or partial test of entrepreneurship education had no significant influence on interest in entrepreneurship. The parents had a significant influence on students’ interest in entrepreneurship, and the results of the F test showed that multiple linear regression models involving both independent variables were acceptable.